Lusitanian amphora contents - Pinto, Inês Vaz (2021)
Roman amphorae produced in Lusitania were usually considered as fish product containers since amphora kilns were mainly known on the coast where they co-existed with fish-salting workshops, and the rare tituli picti known confirmed this assumption. Over the past 25 years the progress in research has brought up new issues: the contents of two flat-base types was questioned and wine was the new content proposed for them; a number of amphora types from the second half of the 1st century BC – early 1st century AD, earlier than the known fish-salting installations, were identified; and different sets of ceramic material from inland sites, some very far from the coast, revealed amphorae in local fabrics that cannot be for fish products. Recent technical advances on content analysis, such as gas chromatography, are an opportunity to clarify contents, and have begun to be applied to Lusitanian amphorae, and the published results are presented. The products likely to be carried in amphorae will also be considered. The contents of Lusitanian amphorae will be discussed relying on existing evidence such as typology, provenance, epigraphy, fish remains and chemical analysis when possible.